Efektivitas Beberapa Metode dalam Analisis Kromosom Tanaman Lai durian (Durio zibethinus x kutejensis) Asal Kalimantan Timur: Effectiveness of Several Methods in Choromosome Analysis of the Lai durian (Durio zibethinus x kutejensis) originated East Kalimantan - Khairunnisa Azizah Salsabila; Muktirianur (Agrifarm : Jurnal Ilmu Pertanian, 2023)
East Kalimantan is one the center of Durio diversity in the world. The high diversity of durio species is a very important for breeding program to select and assembling new superior varieties. The study of the genetic/genomic status of Durio species especially the unindentified endemic plant like lai durian is very important. This study was conducted to find out an effective method for analyzing lai durian (Durio zibhethinus x kutejensis) chromosome as an effort to determine the genome status of the lai durian. This study was conducted at Laboratory of Biotechnology, Faculty of Agriculture, Mulawarman University from April to December 2020. Chromosome analysis used roots and shoots sample to observe chromosome profiles. The treatment of sampling time, time for pre-tretment, fixation, maceration and staining as well as the concentration of the respective solution treatment were applied to the samples. The cell, mitotic stages, and chomosomes profiles were observed under binocular microscope. This study showed in the method root-tips and shoot-tips are collected at 11.00 am, pretreated in 0.002 M 8-hydroyquinoline in refrigerator for 4 hours, fixed in ethanol:glacial acetic acid (v/v 3:1), macerated in 5 N hydrochloric acid at 65°C for 40 minutes, stained in 2% aceto-orcein for 1.5 hours and squashed in 2% aceto-orcein produced the best cell profile. Chromosomes profiles showing dividing cells can be observed in specimens taken from the root-tips and shoot-tips. Prophase, telophase, and cytokinesis stages can also be observed and are most commonly found in root and shoot tip specimens.